2011
DOI: 10.2147/opth.s26035
|View full text |Cite
|
Sign up to set email alerts
|

Iritis and iris atrophy after eyebrow epilation with alexandrite laser

Abstract: PurposeTo report a case of bilateral iritis and transillumination defects after laser hair removal of the eyebrows with an alexandrite laser.MethodsA 41-year-old male presented with bilateral eye pain and mild photophobia 2 days after receiving alexandrite (755 nm) laser epilation of both eyebrows. Examination showed visual acuity of 20/20 in both eyes, 2+ conjunctival injection in both eyes, 1+ cells in the anterior chamber of right eye and trace cells in left eye, poor right pupil dilation, and left pupil wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 7 publications
0
32
0
1
Order By: Relevance
“…Periocular (eyebrow and eyelid) laser epilation should be avoided. Cataracts, iritis, iris atrophy, pupillary distortion, uveitis, photophobia, posterior synechiae, and visual field defects have all been reported despite use of metal protective lenses when treating this region …”
Section: Complications Of Photoepilation and Their Treatmentmentioning
confidence: 99%
“…Periocular (eyebrow and eyelid) laser epilation should be avoided. Cataracts, iritis, iris atrophy, pupillary distortion, uveitis, photophobia, posterior synechiae, and visual field defects have all been reported despite use of metal protective lenses when treating this region …”
Section: Complications Of Photoepilation and Their Treatmentmentioning
confidence: 99%
“…Lin et al and Carrim et al reported patients with pigment dispersion and temporary increased intraocular pressure associated with alexandrite laser epilation of eyebrows [7,8]. Elkin et al described a 41-year-old male who presented with bilateral iritis and iris atrophy without posterior synechiae 2 days after receiving alexandrite laser epilation of eyebrows [9]. Our case is different from their case because of the presence of posterior synechiae without iris atrophy.…”
Section: Discussionmentioning
confidence: 65%
“…Accordingly, previous case reports revealed normal fundus appearance in cases with anterior segment side effects associated with laser hair removal of eyebrows [4,5,7,9]. Nevertheless, Sheikh et al described a 38-year-old woman who presented with unilateral acute anterior uveitis and a diffuse peripheral visual field defect after receiving diode laser hair removal of eyebrows with protective metal goggles.…”
Section: Discussionmentioning
confidence: 99%
“…Elkin ve ark.nın çalışmasında, kaş bölgesine lazer uygulanan 41 yaşındaki erkek olguda bilateral göz ağrısı ve orta derecede fotofobi olduğu belirtilmiştir. 5 Halkiadakis ve ark.nın çalışmasında ise kaş bölgesine uygulanan epilasyondan bir hafta sonra fotosensitivite bulgusunun belirgin olduğu kaydedilmiştir. 6 Shulman ve ark.nın 27 yaşındaki kadın olgusunda, kaş bölgesine uygulanan lazer sonrası her iki gözde iki gün sonra şiddetli ağrı ve fotofobi geliştiğin-den bahsedilmektedir.…”
Section: Discussionunclassified